2009
DOI: 10.1016/j.media.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Constrained non-rigid registration for use in image-guided adaptive radiotherapy

Abstract: A constrained non-rigid registration (CNRR) algorithm for use in prostate image-guided adaptive radiotherapy is presented in a coherent mathematical framework. The registration algorithm is based on a global rigid transformation combined with a series of local injective non-rigid multi-resolution cubic B-spline Free Form Deformation (FFD) transformations. The control points of the FFD are used to non-rigidly constrain the transformation to the prostate, rectum, and bladder. As well, the control points are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Firstly, the prostate and internal structures were manually segmented, as in [16, 33, 34]. Future work will employ an automatic segmentation scheme such as [36] to automatically segment the CG and PZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the prostate and internal structures were manually segmented, as in [16, 33, 34]. Future work will employ an automatic segmentation scheme such as [36] to automatically segment the CG and PZ.…”
Section: Discussionmentioning
confidence: 99%
“…As in [33, 34], in this work manual segmentations of the prostatic structures were used to drive the registration. The prostate and CG were manually delineated on each image (the PZ is simply the subtraction of the two) by an expert radiation oncologist using the Slicer software [35].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Image-guided radiation therapy (IGRT) uses advanced imaging technology such as on-board imaging system to achieve precise and accurate dose delivery. Many studies have reported inter-fractional organ motions and efficacy of IGRT in reducing targeting errors using daily CT images (Den et al 2009, Wang et al 2009, Houghton et al 2009, Pawlowski et al 2010, Varadhan et al 2009, Greene et al 2009). Owing to these techniques, errors in patient set-up and dose delivery can be reduced to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…The goal in radiotherapy cancer treatment is to deliver as much dose as possible to the clinical target volume (CTV), while trying to deliver as little dose as possible to surrounding organs at risk[4,10]. When higher doses are to be delivered, precise and accurate targeting is essential because of unpredictable inter- and intra-fractional organ motions over the process of the weekly treatments, which require accurate nonrigid mapping between treatment and planning day.…”
Section: Introductionmentioning
confidence: 99%